Xylanase production by Trichoderma virens MLT2J2 under solid-state fermentation using corn cob as a substrate - LUSTY ISTIQOMAH; MUHAMMAD NUR CAHYANTO; ZUPRIZAL ZUPRIZAL (Society for Indonesian Biodiversity, 2022)
Abstract. Istiqomah L, Cahyanto MN, Zuprizal. 2022. Xylanase production by Trichoderma virens MLT2J2 under solid-state fermentation using corn cob as a substrate. Biodiversitas 23: 6530-6538. Xylanase is one of non-starch polysaccharide (NSP) degrading enzyme encompass in industrial application like animal feed, food, biofuel, and textile. The objective of this study was to produce and characterize the crude xylanase from MLT2J2 isolate that isolated from coconut husk. Molecular identification revealed that MLT2J2 isolate was identified as Trichoderma virens. The xylanase was produced from Trichoderma virens MLT2J2 (108 spores/g of corncob) using corn cob as substrate with 80% initial moisture content using under solid-state fermentation (SSF) at 30°C for 7 d of incubation. Changes in surface morphology and structure of fermented corn cob were monitored by Scanning Electron Microscope (SEM). Statistical analysis was performed using One-way of analysis of variance (ANOVA) followed Tukey Kramer post hoc test to compare treatment means. Under fermentation parameters the maximum xylanase activity was 181.22 U/g-IDW, loss of dry matter 11.43%, and pH was decreased (4.11) at 5 d of incubation compared to initial pH (5.47). Xylanase was produced between a broad range pH 3-8 and showed acidophilic and mesophilic characteristics (optimum at pH 5,0 and 40°C), and also conserved more than 50% of activity before 4 h of incubation at 30°C and after 5 h at 40°C. The micrographs surface of corn cob before SSF appeared intact and smoother, while turned coarser after SSF, suggestive of a disrupted and more porous surface. These findings reveled that T. virens MLT2J2 could produce extracellular xylanase and potential to disrupt the cell wall of corn cob as a cheap substrate for enzyme production thereby increased the reactive surface area of corn cob for enzymatic in situ hydrolysis.